Is the diagnosis and treatment of depression gender-biased? Evidence from a population-based aging cohort in Sweden - Amaia Bacigalupe; Unai Martín; Federico Triolo; Linnea Sjöberg; Therese Rydberg Sterner; Serhiy Dekhtyar; Laura Fratiglioni; Amaia Calderón-Larrañaga (International Journal for Equity in Health)
Abstract Background As compared to men, older women´s higher rates of depression diagnosis and antidepressant use are widely reported. We aimed to: a) explore whether there is a potential gender bias in the clinical diagnosis of depression and antidepressant prescription in an older population from Stockholm; and 2) analyze if such gender bias differs by patients’ age and socioeconomic status. Methods We used data from the Swedish National Study on Aging and Care in Kungsholmen, SNAC-K (N = 2,941). We compared gender differences in: (a) clinical diagnosis of depression according to the Swedish National Patient Register (ICD-10 codes F32-F34; F412) (“register-based diagnosis”); (b) SNAC-K-based diagnosis of depression, partially gender-blind, using the Comprehensive Psychopathological Rating Scale (CPRS) and the DSM-IV-TR (“SNAC-K based diagnosis); and (c) antidepressant use (ATC code N06A). To analyze the magnitude of the gender bias in the register-based diagnosis of depression and in antidepressant use, and the role of potential moderating factors, prevalence ratios (PR) were calculated using Poisson regression models. Models were run separately by age and social class. Results Women had a 63% higher probability of having a register-based diagnosis of depression (PR = 1.63[1.23–2.15]) and a 79% higher probability of using antidepressants (PR = 1.79[1.34–2.40]). No gender differences were observed in the SNAC-K-based diagnosis of depression. The gender differences in the register-based diagnosis were narrowed, although remained significant, after considering age, depressive symptoms, and health services use (PR = 1.44[1.10–1.88]), as well as the register-based diagnosis in the case of antidepressant use (PR = 1.31[1.04–1.64]). This gender bias was larger among the younger-old and the most advantaged social class. Conclusion A gender-bias was identified in the diagnosis and treatment of depression in older adults within the Swedish healthcare setting, which could imply that health services may be contributing to the medicalization of women’s mental health. Gender-sensitive clinical and public health interventions are essential to reduce gender disparities in mental healthcare, also in old age.